Deterioration in Physical Engine Oil Properties after Different Trip Length - Hameed, Dana Kareem (Kurdistan Journal of Applied Research, 2021)
Fresh engine oils or engine lubricants lose some of their properties during service, engine lubricant deterioration leads to change in oil properties, which ultimately have effect on engine overall performance. Therefore, it is very important to characterize used engine lubricants at different using conditions to check the performance and ability of existing oils, which in turn protects engine parts and also designs new formulations to produce better type of engine oil or improve the existing oil. Therefore, optimizing engine oil lubricant changing time is very important for reducing environmental impact but renewing engine lubricant before it is due rises a customer’s cost. In this study, the most significant parameters such as kinematic viscosity, flash point and fire point were chosen to determine the changes and deterioration in engine oil properties. The oil samples were multigrade fully synthetic with SAE gradation 10W-30 grand ecodrive is used in 5 different passenger cars. Having information about these properties are crucial chemical and physical behaviours of engine oils and for keeping engine’s lifecycle. The test results of this work show that after 10,000 km, 10W-30 Delta NL motor oil brand (special synthetic with API SL) oil properties such as kinematic viscosity at cold start, 40 °C and 100 °C decreased 22.92%, 23.61% and 22.92% respectively. In addition, both flash point and fire point decreased 15.6% and 14.22% consecutively for the base properties, and according to the test results this type of engine oil is suitable to use for 10,000 km.